2009
DOI: 10.1097/prs.0b013e3181954d21
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Regional Posterior Frontal Dura Mater in the Overlying Suture Morphology

Abstract: Regional dura mater plays an important role in suture morphology, and the posterior frontal-associated dura mater possesses potent, pro-osteogenic signals that influence the overlying suture fate. The differential expression pattern of TGF-beta signaling from the dura mater further supports the regional paracrine effect of the dura mater.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…18 Some studies have suggested that regionally differentiated dura mater regulates murine cranial suture fate by providing growth factors to the osteoblasts in the overlying suture complex. 19 Ideally, a dural sample would give information, but it is difficult to obtain.…”
Section: Discussionmentioning
confidence: 99%
“…18 Some studies have suggested that regionally differentiated dura mater regulates murine cranial suture fate by providing growth factors to the osteoblasts in the overlying suture complex. 19 Ideally, a dural sample would give information, but it is difficult to obtain.…”
Section: Discussionmentioning
confidence: 99%
“…Classic studies in which murine cranial sutures typically programmed not to fuse, such as the sagittal suture, are transplanted to suture-fusing dura mater regions and then respond with fusion point to this critical relationship 9 . Similarly, Opperman and colleagues demonstrated that coronal suture devoid of underlying dura mater closed by 3 weeks, in contrast to its natural state to remain patent 10 .…”
Section: Dura Mater Related Pathwaysmentioning
confidence: 99%
“…Interruption of this interaction in the PF suture by interposition of a silicon sheet has been shown to delay suture fusion in rats. 70 Surgical relocation of the SAG suture over PF dura mater and PF suture over SAG dura mater resulted in abnormal SAG suture fusion and PF suture patency. 69,71 Finally, transplantation of COR suture complexes without the underlying dura mater into parietal defects in rats revealed that in the absence of dura mater, the coronal suture fused.…”
Section: The Role Of Dura Matermentioning
confidence: 99%